Method for preparing non-stoichiometric tin oxide nanocrystal from organic tin and application of non-stoichiometric tin oxide nanocrystal in perovskite solar cell
Non-stoichiometric tin oxide nanocrystals were prepared by solvothermal reaction method in alcohol solution, and dispersant was added to the water-alcohol mixed solvent, which solved the problem of insufficient performance of electron transport layer materials in perovskite solar cells, and achieved efficient and stable nanocrystal dispersion and improvement of application performance.
Patent Information
- Application Number
- CN202510028509.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
In existing perovskite solar cells, electron transport layer materials such as TiO2 and ZnO have problems with low charge extraction efficiency, high manufacturing cost and poor interface stability. Although SnO2 has good performance, the high-temperature preparation process limits its application in flexible devices.
Using organotin as the tin source, non-stoichiometric tin oxide nanocrystals are prepared by solvothermal reaction method in the alcohol solution, and a dispersant is added to the water-alcohol mixed solvent to form a stable dispersion liquid.
Low-cost, simple and stable preparation of non-stoichiometric tin oxide nanocrystals is achieved, which improves its application performance and stability in perovskite solar cells.
Smart Images

Figure CN119797418A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a method for preparing non-stoichiometric tin oxide nanocrystals using organic tin and an application of the method in perovskite solar cells. Background Art
[0002] Tin dioxide (SnO2) is a typical wide bandgap semiconductor with a bandgap of about 3.6 eV. It usually has a rutile crystal structure and has good electrical, optical and chemical properties. The wide bandgap structure of SnO2 limits its absorption and utilization efficiency in the visible light region. 2-x ), the electronic structure of tin oxide can be significantly regulated by introducing oxygen vacancies (Vos). Oxygen vacancies not only realize the self-doping effect, but also effectively reduce the band gap of the material, change the electronic band structure, and enhance the carrier migration and conductivity. As the main donor defect, oxygen vacancies not only improve the charge capture characteristics, but also effectively reduce charge recombination, thereby improving the conductivity and stability of tin oxide. Its excellent electrical and optical properties make it widely used in gas sensors, transparent conductive films and other fields.
[0003] Perovskite solar cells (PSCs) are devices that directly convert light energy into electrical energy through the photoelectric effect or photochemical reaction. They are mainly divided into formal PSCs (nip) and trans PSCs (pin). The formal structure of perovskite solar cells usually consists of a transparent conductive substrate, an electron transport layer (ETL), a perovskite light absorption layer, a hole transport layer (HTL) and a metal electrode. At present, the electron transport layer of formal PSCs mainly uses materials such as TiO2, ZnO, and SnO2. Among them, TiO2 has a low charge extraction efficiency at the interface, especially in planar solar cells. In addition, TiO2 needs to be sintered at high temperatures, which not only increases the manufacturing cost, but may also limit its application in flexible devices. ZnO has high electron mobility and good light transmittance, but there is a serious charge recombination problem at the interface between ZnO and perovskite, which reduces the battery efficiency, and the chemical stability of the interface with the perovskite is poor, which easily leads to the decomposition of perovskite at high temperatures. SnO2 is widely used as an electron transport layer because of its low-temperature preparation process, high electron mobility (about 240cm2·V-1·s-1), wide bandgap (3.6-4.0eV), high optical transmittance, good chemical stability and good energy level matching with the perovskite layer. 2-x ) plays an active role in the application of perovskite solar cells. Existing literature (Lee JW, Adu JS, Agbenyeke RE, et al. Ultrathin Oxygen Deficient SnO xFilms as ElectronExtraction Layers for Perovskite Solar Modules[J].Journal of MaterialsChemistry A,2025.) reported an ultrathin oxygen-deficient SnO prepared by plasma modified atomic layer deposition (PMALD) technology. x Thin films as electron extraction layers in perovskite solar modules by regulating SnO x The proportion of oxygen in the device improves the power conversion efficiency and stability of the device, with the efficiency increased from 17.9% to 20.1%, and the initial efficiency of 92% was maintained for up to 2700 hours under extreme temperature and humidity conditions, providing a new way to improve the performance and stability of perovskite solar cells.
[0004] Existing literature (Jiang Qiuhan, Li Xiongping, Wu Jieda, et al. Preparation, characterization and application of a light yellowish brown non-stoichiometric tin oxide conductive powder in conductive coatings [J]. Materials Guide, 2008.) reported a method of preparing a light yellowish brown non-stoichiometric tin dioxide (Sn) using SnCl4·5H2O as raw material, oxalic acid as additive, and ammonia as pH regulator under nitrogen atmosphere at 550℃ for 25min. 2-x ). This method uses tin chloride to react with ammonia water to generate tin hydroxide precipitate, which then reacts with oxalic acid to form a tin oxalate complex, thereby improving the thermal stability of tin oxide and preventing excessive reduction of tin during heat treatment. The precursor is treated at 550°C in a nitrogen atmosphere, oxalic acid decomposes to generate carbon dioxide, and tin hydroxide is converted into tin oxide. In a nitrogen atmosphere, tin oxide forms a non-stoichiometric structure, generating oxygen vacancies or part of the tin being in a low-valent state, and finally a light yellow-brown non-stoichiometric tin oxide (SnO 2-x ). However, the cost of SnCl4·5H2O in this method is high and it is hygroscopic. Excessive use of oxalic acid as an additive may lead to the formation of by-products, affecting the purity of the product. The temperature and atmosphere control during high-temperature heat treatment are difficult, and small fluctuations may lead to non-stoichiometric structure unevenness of the product, affecting the quality of the product. The high reaction temperature and the need for an inert atmosphere make it more difficult to accurately control the reaction, further increasing the difficulty and cost of the experiment. Compared with inorganic tin, organic tin can decompose at a lower temperature, the process is more gentle, and the reaction rate can be effectively controlled, thereby regulating the particle size and morphology of tin dioxide nanocrystals, and the particle growth is more uniform. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing non-stoichiometric tin oxide nanocrystals with organic tin and its application in perovskite solar cells. The non-stoichiometric tin oxide nanocrystals can be stably dispersed in a water-alcohol mixed solvent.
[0006] To achieve the above object, the technical solution of the present invention is as follows: In a first aspect, a method for preparing non-stoichiometric tin oxide nanocrystals by organic tin is provided, comprising the following steps:
[0007] (1) adding organic tin to an alcohol solution and stirring to obtain a uniform mixed solution, so that the concentration of organic tin in the mixed solution is 0.1 to 1 mol / L; the alcohol solution is a mixture of one or more of methanol, ethanol, propanol, and butanol in any proportion;
[0008] (2) Solvent-thermally reacting the mixed solution obtained in step (1) at 150-220° C. (e.g., 150° C., 180° C., 200° C., 220° C., etc.) for 12-36 h (e.g., 12 h, 18 h, 24 h, 36 h, etc.). After the reaction is completed, the solid-liquid phase is separated, and the solid phase is washed and dried with ethanol to obtain non-stoichiometric tin oxide nanocrystals.
[0009] Furthermore, in step (1), the organotin is selected from one of trimethyltin chloride, ethyltin trichloride, triethyltin chloride, butyltin trichloride and propyltin trichloride.
[0010] In a second aspect, a non-stoichiometric tin oxide nanocrystal prepared by the method is provided.
[0011] In a third aspect, a non-stoichiometric tin oxide nanocrystal dispersion is provided, which is prepared by the following steps:
[0012] Dispersing the non-stoichiometric tin oxide nanocrystals in a water-alcohol mixed solvent to obtain a non-stoichiometric tin oxide dispersion;
[0013] A dispersant is added to the non-stoichiometric tin oxide dispersion, and the dispersion is shaken evenly to obtain non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent.
[0014] Furthermore, the ratio of water to alcohol in the water-alcohol mixed solvent is any ratio.
[0015] Furthermore, the alcohol in the water-alcohol mixed solvent is one or more of methanol, ethanol, propanol, butanol, and ethylene glycol mixed in any proportion.
[0016] Furthermore, the mass fraction of the non-stoichiometric tin oxide in the non-stoichiometric tin oxide dispersion is 1% to 20%.
[0017] Furthermore, the dispersant is added in the form of a solution, and the volume ratio of the dispersant to the non-stoichiometric tin oxide dispersion is 1:10-200.
[0018] Furthermore, the dispersant is a mixture of one or more of polyethylene glycol, ammonium citrate, diammonium hydrogen citrate, and quaternary ammonium salt in any proportion.
[0019] In a fourth aspect, the non-stoichiometric tin oxide nanocrystals are used in perovskite solar cells, gas sensors, photocatalysis, transparent conductive films, and OLED devices.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] In this study, organotin compounds were used as precursors and non-stoichiometric tin oxide (SnO) was successfully synthesized by a one-step solvothermal method. 2-x ) nanocrystals, which is low-cost, simple and stable. On this basis, a small amount of dispersant was added and non-stoichiometric tin oxide (SnO) with different concentrations was prepared in a water-alcohol mixed solvent. 2-x ) nanocrystal dispersion. The ions or molecules in the dispersant interact with the surface of non-stoichiometric tin oxide nanocrystals through complexation, electrostatic action, and physical adsorption, which significantly improves the dispersibility of non-stoichiometric tin oxide nanocrystals in a water-alcohol mixed solvent. By optimizing the dispersion conditions, the prepared non-stoichiometric tin oxide (SnO 2-x ) nanocrystals exhibited good transparency and stability in water-alcohol mixed solvents, indicating that their dispersibility in the solution was effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 X-ray diffraction patterns of non-stoichiometric tin oxide nanocrystals prepared in Examples 1 to 4 of the present invention and Comparative Example 1; wherein (A) is a full pattern with a diffraction angle range of 20° to 80°; and (B) is an enlarged pattern with a diffraction angle range of 25° to 35°.
[0023] Figure 2 The present invention shows transmission electron micrographs of non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent prepared in Examples 1-4 of the present invention; wherein (A) is a transmission electron micrograph of tin oxide nanocrystals prepared in Example 1; (B) is a transmission electron micrograph of tin oxide nanocrystals prepared in Example 2; (C) is a transmission electron micrograph of tin oxide nanocrystals prepared in Example 3; and (D) is a transmission electron micrograph of tin oxide nanocrystals prepared in Example 4.
[0024] Figure 3The figures are particle size distribution diagrams of non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent prepared in Examples 1 to 4 of the present invention; wherein, (A) is the particle size distribution diagram of the tin oxide nanocrystals prepared in Example 1; (B) is the particle size distribution diagram of the tin oxide nanocrystals prepared in Example 2; (C) is the particle size distribution diagram of the tin oxide nanocrystals prepared in Example 3; and (D) is the particle size distribution diagram of the tin oxide nanocrystals prepared in Example 4.
[0025] Figure 4 X-ray photoelectron spectra of non-stoichiometric tin oxide nanocrystals prepared in Examples 1 and 4 of the present invention; wherein, (A) is the Sn3d nuclear energy level spectrum of the tin oxide nanocrystals prepared in Example 1; (B) is the O1s nuclear energy level spectrum of the tin oxide nanocrystals prepared in Example 1; (C) is the Sn3d nuclear energy level spectrum of the tin oxide nanocrystals prepared in Example 4; (D) is the O1s nuclear energy level spectrum of the tin oxide nanocrystals prepared in Example 4.
[0026] Figure 5 The digital photos are of the tin dioxide nanocrystalline powder prepared in Example 1(1) of the present invention and Comparative Example 1(1) and the powder dispersed in a water-alcohol mixed solvent in Example 1.
[0027] Figure 6 The UV-visible-near-infrared absorption spectrum and optical band gap diagram of the dispersion prepared by using the non-stoichiometric tin oxide nanocrystals prepared in step (1) of Example 1 of the present invention; wherein (A) is the UV-visible-near-infrared absorption spectrum and optical band gap diagram of the aqueous solvent dispersion; (B) is the UV-visible-near-infrared absorption spectrum and optical band gap diagram of the ethanol solvent dispersion.
[0028] Figure 7 The invention is based on the SnO 2-x Device structure diagram of formal PSCs for ETLs.
[0029] Figure 8 The invention is based on the SnO 2-x JV curve diagram of the formal PSCs of ETLs. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0031] The invention uses organic tin as a tin source and an alcohol solution as a solvent for a solvothermal reaction. The alcohol solvent has reducing properties and strong polarity, and is helpful for generating small-sized and uniform non-stoichiometric tin oxide nanocrystals. By introducing a proper amount of dispersant, the non-stoichiometric tin oxide nanocrystals form a stable dispersion in a water-alcohol mixed solvent.
[0032] Example 1
[0033] Step (1): weighing 2.11 g of butyltin trichloride and adding it to 30 mL of ethanol, stirring for 15 minutes to prepare a uniform butyltin trichloride-ethanol solution, stirring evenly and then adding the mixed solution into a 50 mL high-pressure reactor polytetrafluoroethylene liner to undergo a solvothermal reaction, wherein the solvothermal reaction conditions are: 180° C., 12 hours; the reaction product is washed with deionized water by centrifugation and dried to obtain agglomerated non-stoichiometric tin oxide nanocrystals;
[0034] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in a mixture of water and isopropanol in a volume ratio of 1:1 to obtain a non-stoichiometric tin oxide-water-alcohol mixture dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 4 μl / ml to the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water-alcohol mixture dispersion.
[0035] Example 2
[0036] Step (1): The only difference from step (1) of Example 1 is that the solvent thermal reaction conditions are changed to: 180°C, 24h, and the rest are the same.
[0037] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in a mixture of water and ethanol in a volume ratio of 1:0.5 to obtain a non-stoichiometric tin oxide-water-alcohol mixture dispersion having a non-stoichiometric tin oxide concentration of 4 mg / mL, adding a tetrabutylammonium hydroxide solution to the dispersion in an amount of 12 μL / mL of the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water-alcohol mixture dispersion.
[0038] Example 3
[0039] Step (1): The only difference from step (1) of Example 1 is that the solvent thermal reaction conditions are changed to: 200°C, 12h, and the rest are the same.
[0040] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in deionized water to obtain a non-stoichiometric tin oxide-water dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding polyethylene glycol and ammonium citrate to the dispersion, with the ratio of the added amount to the dispersion being 20 μl / ml respectively, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water solution dispersion.
[0041] Example 4
[0042] Step (1): The only difference from step (1) of Example 1 is that the solvent thermal reaction conditions are changed to: 200°C, 24h, and the rest are the same.
[0043] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in ethanol to obtain a non-stoichiometric tin oxide-ethanol dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 10 μl / ml to the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-ethanol dispersion.
[0044] Example 5
[0045] Step (1): weighing 1.49 g of trimethyltin chloride and adding it to 30 mL of ethanol, stirring for 15 minutes to prepare a uniform trimethyltin chloride-ethanol solution, stirring evenly and then adding the mixed solution into a 50 mL high-pressure reactor polytetrafluoroethylene liner to undergo a solvothermal reaction, wherein the solvothermal reaction conditions are: 180° C., 12 hours; the reaction product is washed with deionized water by centrifugation and dried to obtain agglomerated non-stoichiometric tin oxide nanocrystals;
[0046] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in deionized water to obtain a non-stoichiometric tin oxide-water dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 2 μl / ml to the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water solution dispersion.
[0047] Example 6
[0048] Step (1): weighing 1.81 g of triethyltin chloride and adding it to 30 mL of methanol, stirring for 15 minutes to prepare a uniform triethyltin chloride-methanol solution, stirring evenly and then adding the mixed solution into a 50 mL high-pressure reactor polytetrafluoroethylene liner to undergo a solvothermal reaction, wherein the solvothermal reaction conditions are: 200° C., 12 hours; the reaction product is washed with deionized water by centrifugation and dried to obtain agglomerated non-stoichiometric tin oxide nanocrystals;
[0049] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in a mixture of water and isopropanol in a volume ratio of 1:1 to obtain a non-stoichiometric tin oxide-water dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 2 μl / ml to the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water-alcohol mixed solution dispersion.
[0050] Example 7
[0051] Step (1): weighing 2.13 g of propyltin trichloride and adding it to 30 mL of ethanol, stirring for 15 minutes to prepare a uniform propyltin trichloride-ethanol solution, stirring evenly and then adding the mixed solution into a 50 mL high-pressure reactor polytetrafluoroethylene liner to undergo a solvothermal reaction, wherein the solvothermal reaction conditions are: 200° C., 12 hours; the reaction product is centrifugally washed with deionized water and dried to obtain agglomerated non-stoichiometric tin oxide nanocrystals;
[0052] Step (2): dissolving the non-stoichiometric tin oxide nanocrystals prepared in step (1) in deionized water to obtain a non-stoichiometric tin oxide-water dispersion having a non-stoichiometric tin oxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 2 μl / ml to the dispersion, and shaking evenly to obtain a non-stoichiometric tin oxide nanocrystal-water solution dispersion.
[0053] Comparative Example 1
[0054] Step (1): weigh 0.57 g of sodium stannate tetrahydrate and add it to 30 mL of deionized water. Slowly add 6 mL of acetic acid under stirring to produce a white precipitate. After stirring for 15 min, add the mixed solution into a 50 mL high-pressure reactor lined with polytetrafluoroethylene to undergo a hydrothermal reaction. The hydrothermal reaction conditions are: 180° C., 12 h. The reaction product is washed with deionized water by centrifugation and dried to obtain tin dioxide nanocrystals.
[0055] Step (2): dissolving the tin dioxide nanocrystals prepared in step (1) in deionized water to obtain a tin dioxide-water dispersion having a tin dioxide concentration of 5 mg / ml, adding tetramethylammonium hydroxide to the dispersion in a ratio of 5 μl / ml to the dispersion, and shaking evenly to obtain a tin dioxide nanocrystal-water dispersion.
[0056] Application Example 1
[0057] Based on non-stoichiometric tin oxide (SnO 2-x The formal perovskite solar cells (PSCs) prepared by using electron transport layers (ETLs) of FTO / SnO have the following device structure: 2-xElectron transport layer / perovskite light absorption layer / phenylethylamine iodide (PEAI) layer / solid hole transport layer (Spiro-OMeTAD) / silver electrode (see Figure 7 ).
[0058] First, the FTO substrate was surface treated to ensure good adhesion and wettability. The specific steps were: ultrasonic cleaning of the substrate was performed using glass cleaning fluid, deionized water, and isopropanol, each for 15 minutes, and then the FTO substrate was blown dry with nitrogen and further treated with a UV ozone machine for 5 minutes to improve the surface properties of the substrate. Non-stoichiometric tin oxide (SnO 2-x ) electron transport layer, perovskite light absorption layer, phenylethylamine iodide (PEAI) layer and solid hole transport layer (Spiro-OMeTAD). Finally, a silver electrode was formed on the top of the battery by evaporation for 30 minutes to complete the construction of the device.
[0059] The samples of Examples 1-7, Comparative Example 1 and Application Example 1 were analyzed as follows:
[0060] Figure 1 The X-ray diffraction (XRD) patterns of non-stoichiometric tin oxide nanocrystals prepared in Examples 1 to 4 of the present invention and Comparative Example 1. As can be seen from Figure A, the intensity of the diffraction peak is relatively high, indicating that the sample has good crystallinity. At the same time, the width of the diffraction peak is relatively large, indicating that the crystal size of the sample is extremely small. By measuring the half-width at half maximum (FWHM) of the diffraction peak, the Scherrer formula (D = Kλ / βcosθ) is used for calculation, where the constant K is 0.89; the wavelength λ is 0.15406; and β is the half-width at half maximum of the (110), (101), and (211) crystal planes. According to the above calculations, the average grain sizes of the samples obtained in Examples 1, 2, 3, and 4 are 2.94nm, 4.11nm, 3.59nm, and 5.21nm, respectively. Further magnifying the diffraction pattern, it can be seen from Figure B that compared with the diffraction peaks of Comparative Example 1, the two main peaks of Examples 1 to 4 are shifted to low angles. This shift is usually caused by oxygen vacancies or other defects. As the solvent thermal treatment temperature increases and the reaction time prolongs, the angle of the diffraction peak shift gradually increases, indicating that the oxygen defect concentration in the sample increases.
[0061] Figure 2The transmission electron microscope photos of non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent prepared in Examples 1 to 4 of the present invention. The lattice fringes can be clearly observed from the photos, which indicates that the sample has high cleanliness and good crystallinity. The distribution of the lattice fringes is regular and uniform, which further verifies the highly ordered structure of the prepared nanocrystals. The measurement results show that the interplanar spacings of the tin dioxide nanocrystals on the (110) crystal plane are 0.334nm, 0.338nm, 0.341nm and 0.341nm, respectively, indicating that the prepared non-stoichiometric tin oxide nanocrystals have a highly ordered structure and good crystal quality.
[0062] Figure 3 The particle size distribution diagram of the non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent prepared in Examples 1 to 4 of the present invention. It can be seen that the particle size distribution width of the non-stoichiometric tin oxide nanocrystals prepared in Examples 1 to 4 is narrow, indicating that the grain size is relatively uniform. The average particle sizes of the non-stoichiometric tin oxide nanocrystals prepared in Examples 1 to 4 are 2.62nm, 3.83nm, 3.38nm, and 4.74nm, respectively.
[0063] Figure 4 X-ray photoelectron spectroscopy (XPS) of non-stoichiometric tin oxide nanocrystals prepared in Examples 1 and 4 of the present invention. By analyzing the XPS spectra, it can be seen that the Sn3d spectrum of the non-stoichiometric tin oxide nanocrystals prepared in Example 1 shows two peaks, Sn3d 5 / 2 The nuclear energy level spectrum is located at 487.12 eV, and the binding energy is higher than Sn 2+ The binding energy of Sn is (486.4-486.5eV), which is slightly lower than that of Sn 4+ Binding energy of Sn3d (487.2-487.5eV); 3 / 2 The nuclear energy level spectrum is located at 495.58 eV, and the binding energy is higher than Sn 2+ The binding energy of Sn is (493.3 eV), which is slightly lower than that of Sn 4+ The shift of the Sn3d peak can be attributed to the change in the Sn orbital electron density, which is caused by the Sn 2+ (1.34) and Sn 4+ (1.73) and the different electronegativity and partial oxidation reaction with Sn 2+ -O-Sn 2+ + key replaces Sn 4+ -O-Sn 4+ The sample contains both II and IV oxidation states of Sn. The O1s spectrum shows three peaks at 528.58eV, 530.36eV and 531.64eV, of which the peaks at 528.58eV and 530.36eV are attributed to Sn 2+and Sn 4+ The peak at 531.64 eV is related to the adsorption of oxygen atoms in the oxygen-deficient region caused by oxygen vacancies. The Sn3d spectrum of the non-stoichiometric tin oxide nanocrystals prepared in Example 4 shows two peaks, Sn3d 5 / 2 The nuclear energy level spectrum is located at 486.88 eV, Sn3d 3 / 2 The nuclear energy level spectrum is located at 495.28eV. Similar to the sample in Example 1, it shows that the sample contains both II and IV oxidation states of tin; the O1s spectrum shows three peaks, located at 528.85eV, 530.32eV and 531.49eV, respectively. The peaks of 528.85eV and 530.32eV are attributed to Sn 2+ and Sn 4+ The peak at 530.32 eV is related to the adsorption of oxygen atoms in the oxygen-deficient region caused by oxygen vacancies. From the analysis results, it can be seen that the Sn(II) content of Example 4 is higher than that of Example 2, and the oxygen vacancy ratio (O Ⅲ / (O Ⅰ +O Ⅱ )) is greater than Example 1. This indicates that with the increase of the solvothermal reaction temperature and the extension of the time, the oxygen vacancy content of the non-stoichiometric tin oxide species increases.
[0064] Figure 5 From the digital photographs of the tin dioxide nanocrystalline powder prepared in Example 1(1) and Comparative Example 1(1) of the present invention and dispersed in a water-alcohol mixed solvent of Example 1, it can be seen that the non-stoichiometric tin oxide nanocrystalline powder prepared in Example 1(1) is brownish yellow, and the tin dioxide nanocrystalline powder prepared in Comparative Example 1(1) is white. The tin dioxide nanocrystalline prepared in Example 1 was dispersed in an aqueous solution and an ethanol solution at a concentration of 3 mg / ml, and after adding tetramethylammonium hydroxide at a concentration of 5 μl / ml, the resulting non-stoichiometric tin oxide nanocrystalline-water dispersion and non-stoichiometric tin oxide nanocrystalline-ethanol dispersion both showed a transparent and stable appearance under natural light.
[0065] Figure 6 The UV-visible-near infrared absorption spectra and optical band gap diagram of the non-stoichiometric doped tin dioxide nanocrystals dispersed in the aqueous solution and alcohol solution prepared by using the non-stoichiometric tin oxide nanocrystals obtained in step (1) of Example 1 of the present invention. Among them, the absorbance has a significant absorption peak in the 300-400nm band, and the absorbance gradually decreases in the 400-800nm band. It can still maintain a certain absorption in the entire wavelength range, showing good wide-spectrum absorption characteristics. The calculation of the optical band gap is based on the Tacu formula: αhv 2 =A(hv-E g) is used for calculation, where α is the absorption coefficient, hv is the photon energy, and E g The optical band gap is that the intrinsic semiconductor band gap of common SnO2 is 0-3.6 eV, but due to defect states such as oxygen vacancies, quantum confinement effects and increased carrier concentration, the optical band gap of the non-stoichiometric tin oxide nanocrystals obtained in step (1) of Example 1 in ethanol solution increases to 3.88 eV, and the optical band gap in aqueous solution increases to 3.94 eV.
[0066] Figure 7 The method is obtained in Example 1 of the present invention, based on SnO 2-x The device structure of the formal PSCs of ETLs. The device structure of the formal PSCs is FTO / SnO 2-x Electron transport layer / perovskite absorption layer / phenylethylamine iodide (PEAI) / solid-state hole transport layer (Spiro-OMeTAD) / silver electrode.
[0067] Figure 8 The method is obtained in Example 1 of the present invention, based on SnO 2-x The JV curve of the formal PSCs of ETLs. It can be seen that during the forward scan, the open circuit voltage of the device is 0.969V and the short circuit current density is 24.4mA / cm 2 , the fill factor is 72.1%, and the photoelectric conversion efficiency is 17.06%; when scanning in reverse, the open circuit voltage of the device is 0.989V, and the short circuit current density is 24.4mA / cm 2 , the filling factor is 79.3% and the photoelectric conversion efficiency is 19.29%.
[0068] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing non-stoichiometric tin oxide nanocrystals using organotin, characterized in that: The steps include: (1) adding organic tin to an alcohol solution and stirring to obtain a uniform mixed solution, so that the concentration of organic tin in the mixed solution is 0.1 to 1 mol / L; the alcohol solution is a mixture of one or more of methanol, ethanol, propanol, and butanol in any proportion; (2) subjecting the mixed solution obtained in step (1) to a solvothermal reaction at 150 to 220° C. for 12 to 36 hours; after the reaction is completed, the solid and liquid phases are separated, and the solid phase is washed with ethanol and dried to obtain non-stoichiometric tin oxide nanocrystals.
2. The method according to claim 1, characterized in that: In step (1), the organotin is selected from one of trimethyltin chloride, ethyltin trichloride, triethyltin chloride, butyltin trichloride and propyltin trichloride.
3. Non-stoichiometric tin oxide nanocrystals prepared by the method according to claim 1 or 2.
4. A non-stoichiometric tin oxide nanocrystal dispersion, characterized in that: Prepared by the following steps: Dispersing the non-stoichiometric tin oxide nanocrystals according to claim 3 in a water-alcohol mixed solvent to obtain a non-stoichiometric tin oxide dispersion; A dispersant is added to the non-stoichiometric tin oxide dispersion, and the dispersion is shaken evenly to obtain non-stoichiometric tin oxide nanocrystals dispersed in a water-alcohol mixed solvent.
5. The non-stoichiometric tin oxide nanocrystal dispersion according to claim 4, characterized in that: The ratio of water to alcohol in the water-alcohol mixed solvent is arbitrary.
6. The non-stoichiometric tin oxide nanocrystal dispersion according to claim 4, characterized in that: The alcohol in the water-alcohol mixed solvent is one or more of methanol, ethanol, propanol, butanol and ethylene glycol mixed in any proportion.
7. The non-stoichiometric tin oxide nanocrystal dispersion according to claim 4, characterized in that: The mass fraction of the non-stoichiometric tin oxide in the non-stoichiometric tin oxide dispersion is 1% to 20%.
8. The non-stoichiometric tin oxide nanocrystal dispersion according to claim 4, characterized in that: The dispersant is added in the form of a solution, and the volume ratio of the dispersant to the non-stoichiometric tin oxide dispersion is 1:10-200.
9. The non-stoichiometric tin oxide nanocrystal dispersion according to claim 4, characterized in that: The dispersant is a mixture of one or more of polyethylene glycol, ammonium citrate, diammonium hydrogen citrate and quaternary ammonium salt in any proportion.
10. Use of the non-stoichiometric tin oxide nanocrystals according to claim 3 in perovskite solar cells, gas sensors, photocatalysis, transparent conductive films, and OLED devices.